Sigurnosna analiza sučelja između relejnog uređaja automatskog pružnog bloka i elektroničkog uređaja automatskog željezničko-cestovnog prijelaza - Matanić, Dalibor, inženjer elektrotehnike (Array, 2019)
In the paper safety analysis of interface between electronic type of automatic level crossing device (LC) and relay based device of automatic block system (AB) is conducted for the purpose of indentifying the influence of their joint work on traffic safety. The analysis encompasses all potential failure cases in communication between observed signal-safety devices of AB and LC. Based on the results of the analysis it has been proved that the observed interface meets the safety criteria for application in railway transport, because if any failure occurs the respective signal-safety devices will always shift to a higher level of traffic safety, which is why it is not compromised.